QUALITY PROTEINS FROM EDIBLE INDIGENOUS INSECT FOOD OFLATIN AMERICA AND ASIA - Melo, Virginia; Garcia, Maritza; Sandoval, Horacio; Daniel Jiménez, Héctor; Calvo, Concepción (Emirates Journal of Food and Agriculture, 2011)
There is a serious worldwide nutrition problem due to good quality protein deficiency affecting low income people. Insects are a good alternative, their consumption is all over the world, therefore is important, to improve production and preservation techniques, to market them for available to all population. Insect research has been conducted for more than twenty years, with species from Mexico and other countries of Africa, Asia, Australia and America. Species of 107 edible insects have been studied for their nutritional value and bioavailability. Proximal analysis of five land and aquatic species of insects were performed according AOAC (2000) methods. Results were in this order, grasshoppers, Sphenarium purpurascens Ch protein 71.50%; fat 5.75%; minerals 2.5%; fibre 3.89%; soluble carbohydrates 16.36%. Chicatana ant, Atta Mexicana B protein 66.00%; fat 24.02%; minerals 3.00%; fibre 2.06%; soluble carbohydrates 4.92%. Maguey grub, Aegiale hespheriaris K protein 30.88%; fat 58.55%; minerals 2.29%; fibre 0.12%; soluble carbohydrates 8.16%. Escamol ant eggs, Liometopum apiculatum H protein 40.90%; fat 33.96%; minerals 7.58%; fibre 1.3%; soluble carbohydrates 16.26%. Ahuahutle mosquito eggs are a mixture of Krizousacorixia azteca J and other species, protein 53.60%; fat 4.33%; ash 21.00%; fibre 3.00%; soluble carbohydrates 18.07%. Insects have a good nutritional value and are high in protein with all essential amino acids. Promoting cultivation and preservation techniques will be a good source of income for people who grow these insects not only for their consumption but for commercialization at urban cities.